CORRESPONDENCE DATABASE HANDLING IN UKM PALATIKA USING PHP AND MYSQL - Ferry Fitriawan; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2006)
PALATIKA (Nature Lovers Informatics and Computer Jakarta) is a unit of StudentActivities in Campus STMIK Jakarta STI & K, which moves in the field of NatureLovers. During the time the listing on the SME Palatika correspondence for themanufacture of the report is still performed manually, with the way the notes on paperand on the move through Microsoft Word as the approaching end of theaccountability report so many letters that are not listed.Palatika should use a database that has a very important role in the processing of datasuch as correspondence data. Through this Correspondence Database handling usingPHP (Personal Home Page) and MYSQL is a good solution in solving the problemsfaced during this Palatika secretary is that it can launch a secretary working in thepreparation of reports and correspondence in the correspondence received.